GEJOLAK EMOSI DALAM KARYA SENI LUKIS - YUSUF FADLY ASER, Jupriani, Zubaidah (Universitas Negeri Padang, 2013)
a symptom of one's emotions in daily behavior disclosure, allperceived as feeling sad, happy, happy, disappointed, angry. it affectsthe emotional state of feeling which usually radiates from the state ofgestures or body language. given the human mind and heart todetermine how she faces problems that have and will face. the authorsshow this painting is realist and surrealist. realization of this work iobservation, contemplation, and then visualized into line, color andform of the desired object. work is supported by the authors showequipment and materials, and lead to problems aristik which becameelements of each piece.